Strand 2: Supporting Database Design Learners - Gordon, Adrian; Hall, Lynne (Proceedings of the International Conference on Networked Learning, 1998)
A large body of high quality teaching materials is currently available in the Department of Computing at the University of Northumbria at Newcastle (UNN), in the form of lecture slides and accompanying notes, practical exercises and their model solutions, past examination questions, etc. As part of an on-going effort within the department to make courses available to students in a distance learning mode, this material is currently being adapted to make it suitable to access via the World-Wide Web. However, although ’passive learning’ material such as lecture slides and handouts can be easily adapted for delivery via the Web, the more practical aspects of the courses that we deliver are problematical. A parallel research effort within the department is currently addressing this problem. The initial focus of our efforts has been on adapting a course on Database Design to delivery by Distance Learning mode. The rest of this paper is organised as follows: the first section describes the problems inherent in learning database of systems analysis and design, database design can only truly be learned by practical application of the relevant techniques (McLeod, 1996). In addition to introductory and background material such as that found on the web site, students must also be given the opportunity to apply their knowledge to practical problems in database design. Traditionally, this takes the form of pencil and paper exercises based around pre-prepared scenarios.